Urgensi Kesenian Reyog bagi Mahasiswa IAIN Ponorogo: Perwujudan UU No.12 Tahun 2012 tentang Pendidikan Tinggi (Studi Kasus Unit Kegiatan Mahasiswa PSRM Watoe Dhakon) - Demas Mahardhika Fauzi Ramadhan (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
This study examines the urgency of Reyog art for IAIN Ponorogo students. This is based on law number 12 of 2012 concerning higher education. In this law, students get the right to their talent interests, including in the arts. This concept is also contained in the '45 Constitution article 32 concerning the promotion of national culture which was later born law number 5 of 2017 concerning culture. If a common thread is drawn, all these normatives become problem solvers for the weak intensity of young people in preserving art. In fact, the preservation of art is included in the attitude of hubbul wathon / love of the homeland which is based on the nash of the Qur'an and Hadith, namely in sura an-Nisa verse 66, surah at-Tawbah verse 122, and the hadith of the Prophet narrated by Imam Bukhori about love for the motherland. In line with this, community norms also agree with art preservation efforts. For this reason, this research is formulated in four objectives, namely: (1) Examining the urgency of Reyog art for IAIN Ponorogo students in a normative view. (2) Examining the urgency of Reyog art for IAIN Ponorogo students in a scientific perspective. (3) Assessing the urgency of Reyog art for students based on empirical facts. (4) Examining the urgency of Reyog art for IAIN Ponorogo students through the integration-interconnection paradigm.